Shear strength of reinforced concrete beams with recycled aggregates. Issue 8 (June 2019) - Wardeh, George; Ghorbel, Elhem
This article presents an experimental program on the shear behavior of beams without transversal reinforcement manufactured with natural aggregate concrete and 100% recycled aggregate concrete. The beams were tested under four-point bending for a shear span-to-depth ratio ( a / d ) equal to 1.5 and 3.0. The mechanical properties of two mixes were characterized in terms of compressive strength, splitting tensile strength, and elastic modulus. Three-point bending tests were performed on plain pre-notched samples in order to determine the fracture properties by an inverse analysis of experimental force–crack mouth opening displacement curves using the analytical nonlinear hinge model and a power law strain-softening relationship. The strain-softening law is described by two parameters being, respectively, the power n and the critical crack opening displacement wc . The experimental results show that, for the same class of compressive strength, tensile strength, fracture energy, and the shear strength of recycled aggregate concrete are lower than natural aggregate concrete. The decrease in the fracture energy and the shear strength is consistent with the decrease in the splitting tensile strength of the recycled aggregate concrete mixes compared to the natural aggregate concrete. Critical shear crack theory was adopted to model the shear behavior of beams tested with a / d  = 3.0. For an accurate evaluation of the deformation capacity of tested beams, the nonlinear hinge model for recycled concrete members was extended to recycled concrete sections. For deep beams ( a / d  = 1.5), the strut-and-tie model was used. Finally, comparisons of prediction models to a wide range of experimental data are presented.